Complementary Aspects between COMPLIANCE AND ETHICS: Ethical and Christian Perspectives - Rothlin, Stephan (Asian Horizons, 2012)
Wang Zhile and Jiang Heng (Wang 2010)1 argue that the first priority of Corporate Social Responsibility (CSR) is compliance. Without a strong commitment of firms and other institutions to strict legal adherence, so runs the argument, the whole discourse on Corporate Social Responsibility would be ultimately meaningless. The current article argues that an exclusive focus on compliance remains questionable as it is unlikely to have a decisive impact on human behaviour.